BASED SUSTAINABLE INDIVIDUAL FOREST MANAGEMENT LOCAL FUNCTIONS IN THE DESA LUBUK BERINGIN BATHIN III ULU BUNGO DISTRICT - Norsidi Norsidi (GeoEco, 2019)
Forest Resources Lubuk Beringin Village is an important resource area for people who have various economic, social and environmental functions. The people of Lubuk Beringin Village have their own local wisdom in managing forest resources. This study aims to find out the ways of society in local wisdom-based forest management in the future in the future Lubuk Beringin Village, Bungo Ulu District, Bungo Regency. The method in this study is qualitative research which aims to explore deep social situations. Data collection is done through observation, and in-depth interviews. In-depth interviews were conducted with purposive sampling and snowballing sampling techniques for key informants of the Village Head (Rio), Customary Figures, Religious Leaders and Community Leaders. The results of this study indicate that the people of the Village of Lubuk Beringin, Bathin III Ulu District, Bungo Regency have been guarding and conserving forests based on their local wisdom for decades, firmly upholding the traditions, which were obtained from their ancestors, by observing the procedures for managing land use processes, land clearing , and cultivation and plantation processes, utilization of forest resources and patterns of forest management along with the imposition of sanctions in accordance with customary agreements for communities that have been proven to have violated or deliberately damaged forest resources.